My teacher is an alien - Coville, Bruce (New York, NY : Aladdin Paperbacks, 2005)
After Susan sees Mr. Smith the substitute teacher peel off his face, she knows he's an alien and only Peter believes her. Together they work to save the class from Mr. Smith's horrible plans.
Faculty.
Keywords: Substitute teachers -- Juvenile fiction; Life on other planets -- Juvenile fiction; Schools -- Juvenile fiction; Substitute teachers -- Fiction; Life on other planets -- Fiction; Schools -- Fiction; Science fiction